2012
DOI: 10.1002/ejoc.201201128
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of γ‐Oxo γ‐Aryl and γ‐Aryl α‐Amino Acids from Aromatic Aldehydes and Serine

Abstract: γ‐Oxo α‐amino acids and γ‐aryl α‐amino acids are compounds with very interesting biological properties and are active components of many drug molecules. Oxo amino acids are also used as synthetic precursors for a number of unnatural amino acids and amino alcohols. We report a very efficient synthesis of such compounds through the coupling of aromatic dithianes, prepared from aromatic aldehydes and an iodide derivative of serine. The dithiane groups in compounds thus obtained can be either hydrolyzed or reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…We have already shown that these transformations proceed without a loss of enantiopurity and that the amino alcohols 1 retain the configuration of the serine derivative used. 17 We also synthesized three analogous derivatives 3h-j from L-threonine using the same method (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have already shown that these transformations proceed without a loss of enantiopurity and that the amino alcohols 1 retain the configuration of the serine derivative used. 17 We also synthesized three analogous derivatives 3h-j from L-threonine using the same method (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…17 One of the key intermediates of the synthesis is c-aryl-c-oxo-b-amino alcohols 1, which upon reduction provide 1-aryl-3-amino-1,4-diols. A syn-selective reduction of 1 would provide intermediates 2, which could be used for the synthesis of HPA-12 and its analogues (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxo amino acids were synthesized following a procedure that we had developed for the synthesis of γ‐aryl γ‐oxo α‐amino acids from 1,3‐dithiane derivatives of aromatic aldehydes and an iodide derived from serine . We assumed that a γ‐oxo group would be too close to the peptide backbone and decided to base this study on δ‐ and ε‐oxo amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…We have reported the use of aromatic dithianes for the synthesis of unusual amino acids by coupling them with iodide derivatives of serine . Here, we report a very facile, high yielding and stereospecific synthesis of ferrocene‐containing amino acids from 2‐ferrocenyl‐1,3‐dithiane ( 1 ) using a similar method (Scheme ).…”
Section: Introductionmentioning
confidence: 99%